THE CHARACTERISTICS OF NON-ALCOHOLIC FATTY LIVER DISEASE (NAFLD) PATIENT IN DIABETES MELLITUS AT THE PROF I.G.N.G NGOERAH DENPASAR BALI CENTRAL GENERAL HOSPITAL - Wibowo, Alexandra Victoria; Saraswati, Made Ratna; Mariadi, I Ketut; Rena, Ni Made Renny Anggreni (E-Jurnal Medika Udayana, 2024)
Non-alcoholic fatty liver disease (NAFLD) is a common disease worldwide, including in Indonesia, due to an imbalanced lifestyle. The increase in NAFLD is also caused by the increasing number of diabetes mellitus (DM). This is due to the relationship between the risk factors and pathophysiology of NAFLD and DM. The incidence of NAFLD is increased by 2-3 times in patients with DM. However, data on NAFLD are rarely found in Indonesia.  The purpose of this study was to determine the characteristics of patients with NAFLD in patients with DM. This study is a quantitative observational study using descriptive-analytical methods with total sampling techniques and a cross-sectional approach. The results showed that there were 86 NAFLD samples, of which 26 were diagnosed with DM, with the most frequent age range of 46-65 years (53.5%). The most common gender was male (61.6%). Most of the samples had a body mass index (BMI) above normal (65.1%), but there was a difference between NAFLD with DM (80.8%) and without DM (58.3%). The SGOT and SGPT levels of the samples were the same, namely more normal (62.8%). However, between NAFLD with DM and without DM, different results were obtained, where NAFLD with DM tended to have high SGPT levels (53.8%) while NAFLD without DM tended to be normal (70%). The conclusions of the study are BMI and SGPT levels can be used to distinguish between patients with NAFLD with DM and NAFLD without DM but age, gender, and SGOT levels are not significantly different